Effect of onion extract on microbial and sensory evaluation of fried broiler meat during refrigerated storage (2016)
The flavor and health benefits of onion have been strongly associated to its high content of sulphur compounds and flavonoids acting as, antioxidants and antibiotics. The Microbial and sensory parameters of fried broiler meat marinated in onion extract were evaluated during refrigerated storage. Twenty fresh purple medium sized onion bulbs were purchased, peeled, washed, chopped and oven dried at 4(TC until constant weight was reached. 500ml of 80% Methanol was used to soak 100 grams of the oven dried onion for 24 hrs. Twelve broiler chickens (1.5±0.2 kg) live weight of 56 days age were obtained. 800g of the breast meat was marinated in brine solution and onion extract. The marinade consisted of 16ml of onion extracts and 14grams of table salt added to 4 litres of water. Marinade solution was stored to reach 4°C before breast meats were immersed. Marinated meat was pan fried to an internal temperature of 77°C ±3°C for 15 minutes after 11 hrs of marination and committed to completely randomized design. No growth are recorded for Mould and Yeast. Bacteria were not recorded on the first day but increased progressively from day 2 to 6. Day 6 had the highest coliform and total plate count content of 3.63 MPN/100g and 3.62 logCFU/g respectively. Aroma, flavour, juiciness and overall acceptability reduced progressively while there was no significant difference in colour of fried meat. These results revealed onion extract could inhibit microbial load, improve meat acceptability and shelf life up to 4 days of refrigerated storage.